THE PROCEDURE OF TRANSLATION IN TRANSLATING CULTURAL TERM ON BALI TRAVEL NEWS - Ni Kadek Riska Wirayanti; Ni Md. Diana Erfiani; Km. Tri Sutrisna Agustia (LITERA : Jurnal Bahasa Dan Sastra, 2018)
ABSTRACTThis paper aims to analyzing the cultural term and procedure of translation in translating cultural terms thatfound in Bali Travel News. Theory that applied in this study is from theory of cultural category (Newmark,1988:95) to categorize the cultural term, theory of procedure of translation by Newmark (1988) to analyzethe procedure and componential analysis (Newmark, 1988:114) to show the differences of the feature ofsource language and target language. From the result of the study, there are found (1) the types of culturalterm related to ecology, material culture, social organization and additional terms related to equipment, (2)procedure of translation which are applied in this study are literal, transference, naturalization, culturalequivalent, functional equivalent, descriptive equivalent, modulation and additional.Keywords: cultural terms, procedure of translation, componential analysis, newspaperABSTRACTTulisan ini bertujuan untuk menganalisis istilah budaya dan prosedur penerjemahan dalammenerjemahkan istilah budaya yang ditemukan di Bali Travel News. Teori yang digunakan dalampenelitian ini adalah teori kategori budaya (Newmark, 1988: 95) untuk mengkategorikan istilah budaya,teori prosedur penerjemahan oleh Newmark (1988) untuk menganalisis prosedur dan analisiskomponensial (Newmark, 1988: 114) untuk menunjukkan perbedaan fitur bahasa sumber dan bahasatarget. Dari hasil penelitian, ditemukan (1) jenis-jenis istilah budaya yang berkaitan dengan ekologi,budaya material, organisasi sosial dan ketentuan tambahan yang terkait dengan peralatan, (2) prosedurpenerjemahan yang diterapkan dalam penelitian ini adalah literal, transference, naturalization, culturalequivalent, functional equivalent, descriptive equivalent, modulasi dan addition.Kata kunci: istilah budaya, prosedur penerjemahan, analisis komponen, surat kabar